COMPARISON OF THE DIFFERENT ANASTOMOTIC TECHNIQUES USED IN EMERGENCY ABDOMINAL SURGERY - Aghayev, E.K.; Ismayilova, Z.E.; Hasanov, A.B.; Israfilova, S.B. (World of Medicine and Biology, 2023)
The chosen anastomotic technique plays an important role in the outcome of intestinal resections. However, there is no consensus among surgeons regarding the choice of anastomotic technique. In order to contribute to solving the problem, we conducted a clinical study that included 576 patients. We compared the results of end-to-end and side-to-side anastomoses that were performed in emergency surgeries. In both groups – in our own practice and in the retrospective group side-to-side anastomoses had better results. This can be explained by post-traumatic edema narrowing the anastomosis, separation of the intestinal wall from their mesentery at least 1.5–2 cm, and taking into the suture of the straight intramural arteries close to the suture line in end-to-end anastomoses. It can be concluded that side-to-side anastomoses are recommended during bowel resections in emergency surgery.
Keywords: different anastomotic techniques; end to end anastomoses; side to side anastomoses; postoperative complications; anastomotic leakage